Evaluation of Advertisements Regarding Aphrodisiac Herbal Products in Selected Online Shopping Platforms - Mukhtar, Saidatu Hajar Izam Mohd; Phan, Chia Wei; Alwi, Syireen; Shamsuddin, Noorasyikin (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Aphrodisiac is a substance used to treat sexual dysfunction and boost performance in sexual activity. Aphrodisiac Herbal Products (AHP) was associated with numerous safety issues. The internet has become a pivotal source of health information and platform for purchasing AHP these days. There is already a regulation in place for the advertisement of herbal products; however, the implementation of the regulation is yet to be investigated. Materials and Methods: This study aimed to evaluate the type of information provided in the online advertisements selling AHP and to determine the type of infringements to the local advertising guidelines. An internet search using the local term for AHP was conducted on the largest search engine (www.Google. com). Descriptive analysis was performed on all data. Results: A total of 101 advertisements were included in the assessment. The most common active ingredients of products advertised were Eurycoma longifolia (Tongkat Ali) (16.2%), followed by Uncaria gambir (Gambir Sarawak) (15.8%) and Tribulus terrestris (Tribulus) (6.1%). Most products are from external use (53.5%) and are presented in the form of liquid (34.7%), gel (18.8%) and cream/lotion (5%). All the advertisements included in the study infringed the local advertising guidelines such as the absence of an approval number, including substantiation of the claim and statement of guaranteed safety. The highest product claim stated in the advertisement is “to boost stamina in sexual activity” (26.2%) and “to increase penile size and hardness” (21.5%). Conclusion: The study highlights the urgent need for the authority to impose more stringent control on the advertising and selling of AHP which may cause harmful consequences to the public. Healthcare professionals should also play their role in educating the public and raising awareness of the safety issues related to the use of AHP.
Keywords: Aphrodisiac; Herbal products; Men’s health; Malaysia; Online shopping; Sex; enhancement products; Web advertisement